2015
DOI: 10.2478/jomb-2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Hematological And Biochemical Parameters In Elite Soccer Players During A Competitive Half Season

Abstract: SummaryBackgroundThe purpose of the present study was to report and discuss the hematological and biochemical behavior of elite soccer players, in order to get more insight in the physiological characteristics of these sportsmen and to provide trainers and sports doctors with useful indicators.MethodsNineteen male soccer players volunteered to participate in this study. We followed the young elite soccer players during a competitive half season. Venous blood samples were collected between 9:00 and 10:00 a.m. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 30 publications
(29 reference statements)
11
47
4
1
Order By: Relevance
“…Consensus on the variability in hematological variables over time among athletes and non-athletes ( Joksimovic et al, 2009 ; Nikolaidis et al, 2003 ) or seasonal differences within the same squad ( Andelcovic et al, 2015 ; Manna et al, 2010 ) is lacking. The current work is, to our knowledge, the first providing information about young athletes of Arab origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consensus on the variability in hematological variables over time among athletes and non-athletes ( Joksimovic et al, 2009 ; Nikolaidis et al, 2003 ) or seasonal differences within the same squad ( Andelcovic et al, 2015 ; Manna et al, 2010 ) is lacking. The current work is, to our knowledge, the first providing information about young athletes of Arab origin.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma volume expansion has been shown to occur more rapidly and to a greater extent than the increase in red cell volume following endurance-training programmes (Weight et al, 2007). In two studies a plasma volume expansion was observed in young soccer athletes and older swimmers from baseline to the end of the examined period ( Andelcovic et al, 2015 ; Santhiago et al, 2009 ). However, in our study, plasma volume was decreased in the whole group by 1.4% after 5 months of regular training (T 2 ) and by 4.9% in May (T 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The competitive demand of soccer game may impose strain various physiological systems including the musculoskeletal, nervous and immune and metabolic, which may be reflected in changes in biochemical and hematological parameters (3). Soccer is an endurance-based sport during which athletes require large amounts of oxygen within the different systems of the body in order for them to function (20). Endurance training, like in soccer, may bring about a decrease in erythrocyte, hemoglobin, hematocrit, iron and ferritin concentration, and may lead to changes in the health status of athletes (2).…”
Section: Introductionmentioning
confidence: 99%
“…Los autores afirman que este fenómeno se debió al daño muscular inducido por el acumulo de partidos. En otro estudio con jugadores croatas (Andelkovic, Baralic, Dordevic, Stevuljevic, Radivojevic, Dikic, Radojevic, Stojkovic, 2014), no se observaron cambios significativos a las 6 semanas de competición, pero si hallaron una reducción relevante a las 9 semanas, efecto que pueda deberse a una planificación uniforme durante la primera parte del ciclo competitivo.…”
Section: Discussionunclassified